Atlases Give Global Snapshot of Oceans in the 1990s. Issue 12 (25th March 2014) - Talley, L. D.; Koltermann, K. P.; Gouretski, V. V.; Jancke, K.; Orsi, A. H.; Whitworth, T.; Sparrow, M.; Chapman, P.; Gould, W. J.; Schlitzer, R.
<x xml:space="preserve">Abstract</x> The comprehensive World Ocean Circulation Experiment (WOCE) survey of physical and biogeochemical observations, conducted between 1990 and 1998, was unprecedented in spatial coverage, accuracy, and types of measurements. WOCE data represent the "state of the oceans" during the 1990s, providing a baseline for changes that have been observed subsequently through repeats of selected WOCE sections via the Global Ocean Ship‐Based Hydrographic Investigations Program (GO‐SHIP; http://www.go‐ship.org).